Adolescence endometriosis with abnormal uterine bleeding: A challenging case report - Fita Maulina; Botefilia Botefilia (Majalah Obstetri dan Ginekologi, 2020)
Endometriosis is the presence of endometrial tissue outside the Uterus. The true incidence of endometriosis is not really known, but it is believed that 10-15% of all women in their reproductive age will develop endometriosis and 25-35% of all women who are infertile have endometriosis. The true incidence of endometriosis in adolescents is difficult to quantify and estimates vary among different studies. Although in the past it was assumed that endometriosis presented only after many years of menstruation, studies have shown endometriosis to occur prior to menarche and between 1-6 months after the onset of menarche. A 66% of adult women with endometriosis report the onset of pelvic symptoms prior to age 20. Although etiology and pathophysiology of endometriosis is not well‐understood, but increased rate of retrograde menstruation in patients with heavier menses as with bleeding disorder, is a possible mechanism of disease. Here, we report an early adolescent admitted with dysmenorrhea with bleeding disorder, suspected Von Willebrand disease, presenting abnormal uterine bleeding.